Strategi Peningkatan Kualitas Lulusan Mahasiswa Program Studi Teknik Industri Universitas XYZ Yogyakarta - Emmy Nurhayati; Elly Wuryaningtyas Yunitasari (OPSI, 2020)
The higher level of work competition that requires an academic degree makes an educational institution must improve the quality of graduates. Graduates of Industrial Engineering Study Program as an output of service industry, must have the quality and qualifications required by the users of graduates. Therefore, the college must prepare its students to compete with the ability and competence that can be relied on to obtain a decent job or create small industry. The results of the development of this strategy are expected to realize the students of Industrial Engineering Study Program Universitas XYZ Yogyakarta which has the advantages of: graduating with a short lecture period, high GPA and competent in the field of industrial engineering, has the ability to speak especially foreign languages and reliable IT understanding. The advantages are uses SWOT, EFAS and IFAS approaches. The right strategy recommendation to improve the quality of students is an entrance exam for new students. Equips students of Industrial engineering study Program with professional certification owned, partnering with SME for the creation of new entrepreneurial opportunities, equip students with industrial engineering's software, establishing cooperation with the companies for study excursion, practice and data retrieval or final task internship and also involving the students in local, national and international competitions.